Pollination Ecology and the Rain Forest
DOI: 10.1007/0-387-27161-9_3
|View full text |Cite
|
Sign up to set email alerts
|

Soil-Related Floristic Variation in a Hyperdiverse Dipterocarp Forest

Abstract: A 52 hectare permanent research plot was established in Lambir Hills National Park to enable long-term study of factors controlling the origin and maintenance of tree diversity. In this chapter we summarize some of our recent work on the relationships between floristic variation and edaphic heterogeneity in the Lambir forest. First, we provide a general description of the floristic composition of this hyperdiverse forest. Second, we use a detailed survey of soil chemistry to test whether floristic composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
136
0

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(137 citation statements)
references
References 0 publications
1
136
0
Order By: Relevance
“…Among the plots examined using comparable methods, Sinharaja stands among those with the highest percentage of species demonstrating significant habitat associations: the plot on Barro Colorado Island, Panama, has 33% of its species significantly associated with habitats, those at Mudumalai in India and Korup in Cameroon have 68% each (Anon. 2003, Harms et al 2001, but that at Lambir in Sarawak -also a topographically heterogeneous plot -has 86.8% of species significantly biased with respect to the habitat gradient of the plot (Davies et al 2005). This study may have underestimated the total percentage of habitat specialists at Sinharaja, however, by arbitrarily confining the analysis only to an elevational and topographic gradient.…”
Section: Comparisons With Other Forest Dynamics Plotsmentioning
confidence: 80%
“…Among the plots examined using comparable methods, Sinharaja stands among those with the highest percentage of species demonstrating significant habitat associations: the plot on Barro Colorado Island, Panama, has 33% of its species significantly associated with habitats, those at Mudumalai in India and Korup in Cameroon have 68% each (Anon. 2003, Harms et al 2001, but that at Lambir in Sarawak -also a topographically heterogeneous plot -has 86.8% of species significantly biased with respect to the habitat gradient of the plot (Davies et al 2005). This study may have underestimated the total percentage of habitat specialists at Sinharaja, however, by arbitrarily confining the analysis only to an elevational and topographic gradient.…”
Section: Comparisons With Other Forest Dynamics Plotsmentioning
confidence: 80%
“…Shale-derived soils are clay-rich ultisols generally lacking a humus layer and root mat and have greater nutrient and moisture retention (Baillie et al 2006). Four soil types have been described based on differences in soil chemistry (C, N and P and exchangeable K, Ca and Mg) and elevation (Davies et al 2005). Davies et al (2005) found that of the abundant species at Lambir, 73 % had distributions significantly aggregated on at least one of the four soil types.…”
Section: Methodsmentioning
confidence: 99%
“…Four soil types have been described based on differences in soil chemistry (C, N and P and exchangeable K, Ca and Mg) and elevation (Davies et al 2005). Davies et al (2005) found that of the abundant species at Lambir, 73 % had distributions significantly aggregated on at least one of the four soil types. Here we focus on two soil types, clay and sandy loam, at the extremes of this gradient that differ most in soil properties (Baillie et al 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Davies et al (2005) concluded that a substantial proportion of the plot's tree flora consists of edaphic specialists, and Russo et al (2005) showed that the forests on various soil types differ considerably in their demographic dynamics, with lower mortality and slower growth in sandstone-specialist species.…”
Section: Introductionmentioning
confidence: 99%